Analisis Psikolinguistik terhadap Peran Teknologi Digital dalam Pemerolehan Bahasa Arab pada Generasi Masa Kini - rizki, ahmad rizki; Wahyuni, Sri Wahyuni; Sri Wahyuni; Annisa Avilya; Via Nutil Qomariyah; Idrus Muchsin (Taqdir, 2025)
The growing dependence of the digital generation on various forms of technology in learning Arabic continues to influence their cognitive and affective processes as well as the overall quality of their language production. This study employs a qualitative library research method using a descriptive analytical approach, drawing on literature published between 2020 and 2025 that addresses psycholinguistics, digital technology, and language acquisition. The findings reveal that technology provides multimodal input that strengthens linguistic representations, enhances intake through automated feedback and gamified features, and offers wider opportunities for language production, thereby accelerating the automatization of linguistic skills. Nevertheless, the non-standardized nature of digital input particularly the prevalence of dialectal variations often leads to structural inaccuracies in learners’ output. Emotional factors such as motivation, anxiety, and self confidence are also shaped by platform design. Overall, the effectiveness of technology is determined by the quality of the input it delivers and the psychological readiness of the learners.